Wnt signalling facilitates neuronal differentiation of cochlear Frizzled10-positive cells in mouse cochlea via glypican 6 modulation - Man Wang; Yuechen Han; Weibin An; Xue Wang; Fang Chen; Junze Lu; Yu Meng; Yan Li; Yanqing Wang; Jingxin Li; Chunjie Zhao; Renjie Chai; et al. (Cell Communication and Signaling)
Abstract Degeneration of cochlear spiral ganglion neurons (SGNs) leads to irreversible sensorineural hearing loss (SNHL), as SGNs lack regenerative capacity. Although cochlear glial cells (GCs) have some neuronal differentiation potential, their specific identities remain unclear. This study identifies a distinct subpopulation, Frizzled10 positive (FZD10+) cells, as an important type of GC responsible for neuronal differentiation in mouse cochlea. FZD10 + cells can differentiate into various SGN subtypes in vivo, adhering to natural proportions. Wnt signaling enhances the ability of FZD10 + cells to function as neural progenitors and increases the neuronal excitability of the FZD10–derived neurons. Single-cell RNA sequencing analysis characterizes FZD10-derived differentiating cell populations, while crosstalk network analysis identifies multiple signaling pathways and target genes influenced by Wnt signaling that contribute to the function of FZD10 + cells as neural progenitors. Pseudotime analysis maps the differentiation trajectory from proliferated GCs to differentiating neurons. Further experiments indicate that glypican 6 (GPC6) may regulate this neuronal lineage, while GPC6 deficiency diminishes the effects of Wnt signaling on FZD10–derived neuronal differentiation and synapse formation. These findings suggest the critical role of Wnt signaling in the neuronal differentiation derived from cochlear FZD10 + cells and provide insights into the mechanisms potentially involved in this process.